If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1(2m + 5) = 4 + 2m + -15 Reorder the terms: 18 + -1(5 + 2m) = 4 + 2m + -15 18 + (5 * -1 + 2m * -1) = 4 + 2m + -15 18 + (-5 + -2m) = 4 + 2m + -15 Combine like terms: 18 + -5 = 13 13 + -2m = 4 + 2m + -15 Reorder the terms: 13 + -2m = 4 + -15 + 2m Combine like terms: 4 + -15 = -11 13 + -2m = -11 + 2m Solving 13 + -2m = -11 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 13 + -2m + -2m = -11 + 2m + -2m Combine like terms: -2m + -2m = -4m 13 + -4m = -11 + 2m + -2m Combine like terms: 2m + -2m = 0 13 + -4m = -11 + 0 13 + -4m = -11 Add '-13' to each side of the equation. 13 + -13 + -4m = -11 + -13 Combine like terms: 13 + -13 = 0 0 + -4m = -11 + -13 -4m = -11 + -13 Combine like terms: -11 + -13 = -24 -4m = -24 Divide each side by '-4'. m = 6 Simplifying m = 6
| 6(4x+15)+13x-12= | | 31/5+x=6 | | a=-2(1.4c)+4c | | 18080-5x=8 | | -x-6y=-5 | | 21/5+x=6 | | 4(x-80)+10=-10 | | 4(5x+6)+7(12-x)= | | 3+z=-19 | | -1+a=0.5 | | 69-(7x+4)=7(x+5)+x | | [-x]=-1 | | 9x-18=40+3x | | 7-12x/4 | | 2x+3x+9=8 | | 6x^2+28x+26=0 | | 10=-12-e | | (7x+13)+(7x-2)= | | -2(y-3)=y+4s | | 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 |